The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.bjane.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a smartphone to test laryngoscope's light and an audit to our laryngoscopes using an ISO standard

Abstract: The tested smartphone has enough accuracy to perform light measurement in laryngoscopes. We believe this is a step further to perform an objective routine check to laryngoscope's light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The mobile phone app was not found to be accurate when compared to a lux meter. This is in keeping with a previous comparison of various free apps to a lux meter, 15 but is in contrast to the study by Machado et al 6 The author specified that the app used would have an accuracy of 80% in the range of 5 -10 000 lux, but it is not mentioned which app was used, if the app was purchased, and if any other accessories were required to ensure accuracy.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The mobile phone app was not found to be accurate when compared to a lux meter. This is in keeping with a previous comparison of various free apps to a lux meter, 15 but is in contrast to the study by Machado et al 6 The author specified that the app used would have an accuracy of 80% in the range of 5 -10 000 lux, but it is not mentioned which app was used, if the app was purchased, and if any other accessories were required to ensure accuracy.…”
Section: Discussionsupporting
confidence: 54%
“…Their findings showed that the lux meter app readings were variable, and were not consistent with those taken by the lux meter. 15 In contrast, a study by Machado et al 6 measuring illuminance of laryngoscopes using an app and a lux meter showed that the app was as accurate as a lux meter. The authors describe the type of phone used in the study (Motorola ® Moto G XT1068), but not the android app chosen, or if any other accessories were required.…”
Section: Foundmentioning
confidence: 97%
See 1 more Smart Citation